Analisis Konsep Fisika pada Kearifan Lokal Petik Laut Situbondo sebagai Sumber Belajar Fisika di SMA - Nurul Safitri, Aida; Matarani Salma, Vidya (Jurusan Teknik Sipil, Politeknik Negeri Ketapang, 2023)
Local wisdom is a view of life, knowledge, understanding and belief as well as habits carried out by local people in the form of activities. Local wisdom of the Situbondo people is defined as activities owned by the Situbondo people which have been proven to be preserved until now. One example is petik laut tradition. Petik laut tradition is a traditional ceremony or ritual performed by throwing offerings into the sea. There are many physical concepts in Petik laut tradition so that the integration of petik laut local wisdom into physics learning in high school is very necessary. This study aims to analyze the physical concepts that exist in petik laut tradition that can be used as learning resources in high school. This research is a qualitative research. Data collection techniques using interviews, observation and literature study. Data were analyzed descriptively. The results of this study were obtained from petik laut tradition by identifying physics concepts, especially in Newton's II and III Laws, Pressure, Archimedes' law and waves. Thus, the analysis of physics concepts in petik laut tradition can be used as an alternative source of learning physics in high school